ANALISIS PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PADA LEMBAGA PENDIDIKAN - Sahrul; Muljono Damopolii (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the concept of the Education Management Information System (SIMP) in supporting and optimizing the governance of educational institutions. Furthermore, this study examines the urgency of developing SIMP to improve the quality of educational services and identifies various educational administration digitalization platforms implemented in the current educational institution ecosystem. This study uses a library research method by reviewing 20 relevant references sourced from scientific journals, books, e-books, and credible digital documents. The research process was carried out systematically, including the stages of topic determination, focus limitation, data source collection, and the preparation of a comprehensive report. Data validity testing was carried out through source triangulation techniques by comparing various literatures to ensure objectivity, analytical depth, and the validity of the research results. This study concludes that the implementation of the Education Management Information System (SIMP) through various digital platforms of the Ministry of Religious Affairs (EMIS, SIKURMA, SIMPATIKA, e-RKAM, and SIMSARPRAS) is a strategic instrument that has succeeded in significantly transforming institutional governance. This digitalization goes beyond simply computerizing data, but also integrates technology and human resources to create a valid, transparent, and accountable data ecosystem. This integrated database has been proven to improve managerial effectiveness, operational efficiency, and decision-making accuracy, from the planning stage to program evaluation. Overall, SIMP is a key foundation for realizing a modern, high-quality, adaptive, and sustainable education governance system.